Re-analysis of the (100), (001), and (020) rotational structure of SO2 on the basis of high resolution FTIR spectra; Journal of Quantitative Spectroscopy and Radiative Transfer; Vol. 130 - Ulenekov (Ulenikov) O. N. Oleg Nikolaevich; Onopenko G. A.; Gromova O. V. Olga Vasilievna; Bekhtereva E. S. Elena Sergeevna; Horneman V.-M. (2013, 2013)
Title screen